Time for cranberries - Detlefsen, Lisl H. (Roaring Brook Press, 2015)
From the cranberry bog to the Thanksgiving table, join Sam and his family as they harvest a classic American fruit. When the vines hang heavy with berries that the autumn winds have turned deep red, it's time for cranberries, and Sam is finally old enough to help with the harvest! This charming, lyrical picture book follows Sam and his family as they raise the water in the bog, pick the cranberries, and gather the fruit for processing. It's a story of modern family farming in action, showing readers where their food comes from but mostly delighting them along the way. --